2019
DOI: 10.31234/osf.io/d936f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional connectivity predicts the dispositional use of expressive suppression but not cognitive reappraisal

Abstract: Previous research has identified specific brain regions associated with regulating emotion using common strategies such as expressive suppression and cognitive reappraisal. However, most research focuses on a priori regions and directs participants how to regulate, which may not reflect how people naturally regulate outside the laboratory. Here, we used a data-driven approach to investigate how individual differences in distributed intrinsic functional brain connectivity predict emotion regulation tendency. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(89 reference statements)
0
3
2
1
Order By: Relevance
“…A positive relation between expressive suppression and cortical thinning use was shown before, albeit only in males (Vijayakumar et al, 2014). Contrary to our findings, sex differences have been demonstrated in relations between indices of brain function and structure and expressive suppression in several studies (Burr et al, 2019;Li et al, 2017;Vijayakumar et al, 2014;Welborn et al, 2009). Still, there is a considerable overlap in regions implicated in expressive suppression in this study and other structural imaging studies of expressive suppression (Li et al, 2017;Welborn et al, 2009).…”
Section: Expressive Suppression and Cortical Thickness Developmentcontrasting
confidence: 96%
See 2 more Smart Citations
“…A positive relation between expressive suppression and cortical thinning use was shown before, albeit only in males (Vijayakumar et al, 2014). Contrary to our findings, sex differences have been demonstrated in relations between indices of brain function and structure and expressive suppression in several studies (Burr et al, 2019;Li et al, 2017;Vijayakumar et al, 2014;Welborn et al, 2009). Still, there is a considerable overlap in regions implicated in expressive suppression in this study and other structural imaging studies of expressive suppression (Li et al, 2017;Welborn et al, 2009).…”
Section: Expressive Suppression and Cortical Thickness Developmentcontrasting
confidence: 96%
“…Given gender differences in emotional display rules (Safdar et al, 2009), the degree to which these observed differences are biologically or socially driven is unknown. Moreover, fMRI studies (Burr et al, 2019;Whittle, Yü cel, Yap, & Allen, 2011) and structural MRI studies of emotion regulation have indicated group-level sex differences; e.g., greater cortical thinning in predominantly prefrontal cortices in adolescent females related to higher cognitive reappraisal and lower expressive suppression (Vijayakumar et al, 2014). Expressive suppression was also linked to thinner cortices of the superior frontal gyrus and less gray matter volume of the right dorsolateral PFC in males, and more gray matter volume in mPFC in females (Li et al, 2017;Wang et al, 2017).…”
Section: Development Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings not only contrast with the two studies on which we based our a priori hypotheses (Uchida et al, 2015 ; Picó-Pérez et al, 2018 ), they also contradict several other studies that have identified patterns of intrinsic functional connectivity that differ between the dispositional use of ER strategies or are associated with experiential and neuronal reappraisal success (Morawetz et al, 2016 ; Pan et al, 2018 ; Burr et al, 2020 ). Common to these studies is that regions in the default mode network have been identified.…”
Section: Discussioncontrasting
confidence: 99%
“…Common to these studies is that regions in the default mode network have been identified. Particularly, the latest study by Burr et al ( 2020 ) used the largest sample up to date ( N = 1,316) in a data-driven, theory-free approach and found that intrinsic connectivity of the default mode network was associated with dispositional use of suppression (but not reappraisal). Critically, the authors used general functional connectivity (GFC, Elliott et al, 2019 ) to leverage shared features of task and resting-state fMRI and circumvent reported reliability issues of resting-state measures (e.g., Noble et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%